Syphilitic balanitis of Follmann - Alexandru Oanţă, Marius Irimie (Philadelphia, Lippincott, 2014)
Background: Syphilitic balanitis of Follmann (SBF) is a rare condition that is considered as manifestation of primary syphilis. Materials and methods: A 28-year-old heterosexual male patient was consulted for a diffuse indurated dark red erythema of the glans penis accompanied by bilateral inguinal lymphadenopathy. Serological tests for syphilis were found positive. Treatment consisting of a single intramuscular administration of 2.4 million units of benzathine-penicillin was followed by complete disappearance of erythema and induration of the glans within two weeks. Results: Syphilitic balanitis of Follmann presents with variable clinical appearances, and primary chancre may be absent, associated with, or occur after the balanitis. Usually the inguinal lymphadenopathy is present, and syphilitic serology is positive or is going to become positive. Treatment is identical to that of primary syphilis. Conclusion: The recrudescence of syphilitic infection requires exclusion of SBF from the diagnosis of balanitis.